Análisis de las exportaciones de minerales 2017-2021: TLC entre Perú y China - Shacamajo, Jhunior (2022)
Currently, the accelerated growth of Chinese industries has allowed an increase in the consumption of minerals such as gold, iron, lead, copper and zinc. The objective of this article was to analyze the exports of the free trade agreement (FTA) between Peru and China from 2017 to 2021. The study is of an applied type because the existing knowledge on exports from Peru (PromPeru) was used. Same that determines the growth of exports on a progressive and gradual scale, in this sense China seeks to ensure the stability of the supply of resources, for the sustainability of its productive chain, in addition, the research is a descriptive type analysis documentary post facto. The results show that the minerals described are the most sent to the Asian country and the spike in remittances occurred from 2017. Finally, the FTA allows a boost to the growth of the national economy, since China is a very large market and this determines the level of exports of our country, therefore, it is suggested to analyze in more detail the exports, since it is necessary statistical analysis with hypothesis testing, the confidence level and the analysis should focus on a specific item, which allows comparing data from other countries in South America with Peru.